2019
DOI: 10.1111/pce.13518
|View full text |Cite
|
Sign up to set email alerts
|

The role of amino acid metabolism during abiotic stress release

Abstract: Plant responses to abiotic stress include various modifications in amino acid metabolism. By using a hydroponic culture system, we systematically investigate modification in amino acid profiles and the proteome of Arabidopsis thaliana leaves during initial recovery from low water potential or high salinity. Both treatments elicited oxidative stress leading to a biphasic stress response during recovery. Degradation of highly abundant proteins such as subunits of photosystems and ribosomes contributed to an accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
196
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(208 citation statements)
references
References 74 publications
9
196
1
2
Order By: Relevance
“…Several primary metabolites, including amino acids, sugars, and organic acids, have been reported to accumulate and function during environmental stress ( Rai, 2002 ; Kaplan and Guy, 2004 ; Rosa et al , 2009 ; Bitrián et al , 2012 ; Nakabayashi and Saito, 2015 ; Drincovich et al , 2016 ; Batista-Silva et al , 2019 ). The gene expression analysis provided a strong argument that cellular stress increases during leaf development and we expected the abundance of protective metabolites or stress marker metabolites to reflect this too.…”
Section: Resultsmentioning
confidence: 99%
“…Several primary metabolites, including amino acids, sugars, and organic acids, have been reported to accumulate and function during environmental stress ( Rai, 2002 ; Kaplan and Guy, 2004 ; Rosa et al , 2009 ; Bitrián et al , 2012 ; Nakabayashi and Saito, 2015 ; Drincovich et al , 2016 ; Batista-Silva et al , 2019 ). The gene expression analysis provided a strong argument that cellular stress increases during leaf development and we expected the abundance of protective metabolites or stress marker metabolites to reflect this too.…”
Section: Resultsmentioning
confidence: 99%
“…It was also interesting to find the remarkable increase in certain amino acids in Mut68, mainly those of proline, glutamine, and tryptophan. Among these, proline is well known for its association with stress tolerance [46], which may have been induced by the lack of trehalose in Mut68. Tryptophan can also be involved in stress response as a precursor to hormones such as melatonin and auxin [55], which can be involved in stress tolerance as well as developmental regulation in animals and plants.…”
Section: Discussionmentioning
confidence: 99%
“…Mut68 contains greatly reduced trehalose contents, which can render it imbalanced in stress-related amino acids. In general, certain amino acids accumulate under stress conditions, as reported in plants [46], and certain stress conditions are known to induce lipid accumulation in microalgae [47]. Therefore, we also included amino acids in the metabolite profiling using GC-MS ( Fig.…”
Section: Further Metabolite Profiling Of Amino Acidsmentioning
confidence: 99%
“…Abiotic stress tolerance can be achieved by proline (Pro) synthesis to counter osmotic stress 34 , making Pro a stress indicator. Besides Pro and its derivatives, glycine betaine (GB), valine (Val), isoleucine (Ile) and aspartic acid (Asp) are major organic osmolytes that accumulate in a variety of plant species in response to environmental stresses such as drought, salinity, extreme temperatures, UV radiation and heavy metals 35 . A meta-study on the metabolic response of Arabidopsis to abiotic stresses revealed that lysine (Lys) and threonine (Thr) are also induced under several stress conditions 36 .…”
Section: Discussionmentioning
confidence: 99%